PENGARUH SISTEM BAGI HASIL DAN PENDIDIKAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHAN MAHASISWA IAIN PALOPO - Zainuddin S (MUAMALAH, 2015)
Development of entrepreneurship spirit is one obligation for universities to reduce the  rate of unemployment by providing knowledge of intellectual entrepreneurship and economics that is based Islam product knowledge for results is a product of Islamic banking in addressing capital of Muslim businessmen. But in fact Alumni IAIN Palopo not maximized in creating entrepreneurship mentality alumni. Results of multiple linear regression analysis partial (t-test) value t count X1 and X2 variables namely 1,720 and 1,443 greater than the value of the t-table is 1996,. contributing variable profit-sharing system and entrepreneurial education to variable interest in entrepreneurship IAIN students Palopo is 6.8%. The rest was influenced by other variables not be modeled in this study